A localização da indústria de transformação brasileira nas últimas três décadas - Souza, Filipe Lage de (2002)
The purpose of this dissertation is to understand the spatial evolution of the industrial sector in Brazil over the last three decades. At first, the goal is to verify how specialized and concentrated the Brazilian states are in industrial terms with the help of the Krugmam and Gini indices. The Brazilian states are then separated into four groups by the cluster-analysis method of K-means. Through a usual inner product within the vector of the distribution of industrial production by sectors in the states, and the vector of some industries characteristics (called the Industry Characteristic Bias, or ICB), the second part analyzes which type of industry the state’s industrial sectors are concentrating and/or specializing in. A principal components analysis is made in these ICB’s, and the components are used to verify which states are more alike. The goal then changes to investigate how geographically concentrated the industrial sectors are. The Gini Index is also used in this objective, but the Venables Index better captures how these industrial sectors are concentrated in a spatial view, where the distances between the states are not negligible. The industrial sectors are separated into three groups by a cluster analysis in which the variables are the principal components of the industries’ characteristics. Using the State Characteristic Bias (SCB), the industrial sectors are then analyzed from the perspective of which type of states these sectors choose. To see how these two viewpoints, or rather, the characteristics of the states and those of the industries influence the location of the industrial sectors within Brazil, an econometric model proposed by Midelfart-Knarvik et al. (2000) is estimated with the Brazilian data. In this model, it is possible to investigate how the interaction of industry and state characteristics can determine where different industries are. The principal results show that the higher investiments in infraestructure in the 70’s and the liberalization of the 90’s were importants in the location of the brazilian industry.